Pendayagunaan Dana Zakat, Infaq, dan Shadaqah melalui Pemberdayaan Petani pada Lembaga Amil Zakat Al-Azhar Surabaya - Putri Rizky Maisaroh; Sri Herianingrum (Universitas Airlangga, 2019)
The purpose of this study to determine the utilization of ZIS funds by LAZ Al-Azhar Surabaya in community groups in Laharpang Hamlet through economic empowerment. The research is descriptive qualitative with the case study method.LAZ Al-Azhar by using qualitative method. interviews were conducted with five respondents consisting of two parties from LAZ Al-Azhar and three group members. The data used are primary data and secondary data. The results of the study indicate that the utilization of Al-Azhar ZIS LAZ funds in the Lamor Kelud Sejahtera Community Self-Help Group (SHG) was carried out through the Million Empowerment Program. Empowerment of SHG provided is in the form of assistance, supervision, capital loans, and Joint Business Groups (KUB). This is evidenced by the increase in revenue mustahiq, smoothness installment payments as well as the ability to sadaqah.Keywords: Utilization of Zakat Infaq Shadaqa, LAZ Al-Azhar, Empowerment, Lamor Kelud Sejahtera KSM.